Green synthesis of silver nanoparticles and its combination with Pyropia columbina (Rhodophyta) extracts for a cosmeceutical application - González-Conde, Mercedes; Vega Sánchez, Julia; López-Figueroa, Félix; García-Castro, Miguel; Moscoso, Ana; Sarabia-García, Francisco Ramón; López-Romero, Juan Manuel (MDPI, 2023)
We report the green synthesis of silver nanoparticles (AgNPs) by using daisy petals (Bellis perennis), leek (Allium porrum) and garlic skin (Allium sativum) as reducing agents and water as solvent. AgNPs are obtained with high monodispersity, spherical shapes and size ranging from 5 to 35 nm and characterized by UV-Vis and TEM techniques. The obtained yields in AgNPs are in concordance with the total phenolic content of each plant. We also study the incorporation of AgNPs in combination with the red algae Pyropia columbina extracts (PCE) into cosmetic formulations and analyze their combined effect as photoprotective agents. Moreover, we carry out the inclusion of the PCE containing mycosporine-like amino acids (MAAs), which are strong UV-absorbing and antioxidant compounds, into β-cyclodextrin (βCD) and pNIPAM nanoparticles and analyze stability and release. The thermoresponsive polymer is grown by free radical polymerization using N-isopropylacrylamide (NIPAM) as the monomer, N,N′-methylenebisacrylamide (BIS) as the cross-linker, and 2,2′-azobis(2-methylpropionamidene) (V50) as the initiator, while βCD complex is prepared by heating in water. We evaluate the nanoparticle and βCD complex formation by UV-Vis and FT-IR, and NMR spectroscopies, respectively, and the nanoparticles’ morphology, including particle size, by TEM. The cosmetic formulations are subsequently subjected to accelerated stability tests and photoprotective analyses: a synergistic effect in the combination of AgNPs and PCE in photoprotection was found. It is not related to a UV screen effect but to the antioxidant activity, having potential against photoaging.
Keywords: Ajo; Nanoparticulas -- Plata; Rodofíceas; Cosmética-Industria; Silver nanoparticles; Green synthesis; Daisy; Leek; Garlic; Pyropia columbina; Photoprotectors; Encapsulation; NIPAM